An assessment of the impact of construction work on fine particulate matter in the University of Jordan: A PIXE study. (29th July 2019) - Sa'adeh, Hanan; Aburugia, Sara; Chiari, Massimo
Abstract : Aerosol sampling was carried out prior to and during an active construction work at the University of Jordan in Amman, Jordan. Elemental characterization for 60 PM2.5 samples was performed by particle‐induced X‐ray emission (PIXE) technique at the LABEC laboratory of INFN in Florence, Italy. Twenty three elements (Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Br, Rb, Sr, Zr, Ba, and Pb) were detected, and their concentrations were assessed during three sampling periods, namely, "No Construction, " "Pouring Concrete, " and "Bleaching." The results showed higher concentrations of soil‐related elements and lower concentrations of anthropogenic‐related elements during construction periods compared with their concentrations before construction. Soil‐related elements showed very low enrichment factor (EF) and high correlation coefficients during all sampling periods. Anthropogenic‐related elements were very much enriched and correlated only during the first sampling period "No Construction."